WIWA PAWINTENAN CEREMONY IN THE SYSTEM AGURON-GURON IN GRIYA AGUNG BANGKASA BONGKASA VILLAGE, ABIANSEMAL DISTRICT, BADUNG REGENCY - Putu Eddy Purnomo Arta; I Nengah Duija; Ida Bagus Gede Candrawan (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2024)
Pawintenan Wiwa can be said to be at odds with the Balinese tradition of Pawintenan, which is determined according to four methods (heredity, election, nyanjan, and lekesan), but still upholds Balinese traditions by using various ceremonial facilities and rerajahan script. To obtain data, a qualitative approach was used which was presented in qualitative descriptive form. The research results briefly show that: 1) The Pawintenan Wiwa ceremony aims to achieve religious goals, increase spiritual achievements, carry out boarding chess, serve the people, and referential functions. 2) The aguron-guron mechanism includes the recruitment of mewinten candidates, the learning system, the relationship between teachers and students; teachings or curriculum, student code of ethics, and sanctions. The Wiwa Pawintenan system includes processions, rituals, authority. 3) The implications of the Pawintenan Wiwa ceremony are presented in an analysis of theological implications, social implications, economic implications, symbolic capital.